ANALISIS YURIDIS HAKIM TERHADAP KEDUDUKAN WALI DALAM PERMOHONAN PERKARA ISBAT NIKAH (STUDI PUTUSAN PENGADILAN AGAMA KABUPATEN MALANG Nomor 0991/Pdt.P/2019/PA.Kab.Mlg) - Yudha Dwi Anggono; Ahmad Subekti; Humaidi Kahari (Jurnal Hikmatina, 2021)
Marriage is a sacred event that can form the smallest unit, namely the family, in this case it has the main joint for the development of a society, nation and state. Marriage is a sacred, strong and solid agreement to live together legally. Forming a family that is eternal, polite, caring, loving, peaceful and peaceful. In Indonesia, it is regulated according to Law no. 1 of 1974 concerning marriage and the Compilation of Islamic Law (KHI). The existence of a guardian as a pillar of marriage as contained in the thoughts of Malikiyyah, Syafi'iyyah and Hanabilah. Based on the decision of the Malang Regency Religious Court Number 0991/Pdt.P/2019/PA.Kab.Mlg, there has been a rejection of the case in which the applicant did not provide a clear reason for the guardian after his father was absent, namely his grandfather, in fact his grandfather is still alive. The focus of the research in the discussion of the proposed thesis is the position of the guardian, the analysis of the judge's considerations and the solutions offered by the judge to the case number 0991/Pdt.P/2019/PA.Kab.Mlg.